Feasibility of Anesthesia-Free Ureteroscopic Lithotripsy in Elderly Patients with Urinary Tract Infections - Duk Yoon Kim; Hyun Jin Jung; Eun Kyoung Yang; Won Yeol Cho (Urogenital Tract Infection, 2023)
Purpose Patients with underlying diseases, particularly in the elderly, urinary tract obstruction with a ureter stone would progress to severe conditions. Some of them have poor general conditions to endure anesthesia. Therefore, this study validated the feasibility of ureteroscopic stone removal without anesthesia for elderly patients with ureter stones who were under impending septic conditions or severe urinary tract infections. Materials and Methods Thirty-four patients (16 males and 18 females) were included in this study. All of them had serious problems, making it difficult to endure anesthesia. Most of them were inserted pre-operative percutaneous nephrostomy catheter, and ureteroscopic lithotripsy was performed successfully after intravenous analgesic injection (pethidine 25 mg). Results The mean age was 71.8±10.84 years. The locations of the stones were upper ureter in 11, mid-ureter in 6, and lower ureter in 17 cases. Urine and blood cultures identified bacteria from 17/34 patients. Escherichia coli was the most common (10/17), followed in order by Klebsiella pneumoniae and Staphylococcus epidermidis in 5 and 2 cases, respectively. Most patients had an abnormal white blood cell count (19,400±4,233.3/ml) and elevated C-reactive protein levels (110.3±83.6 mg/L). No patient had to stop the operation because of intolerable pain. The mean of the visual analog pain scale was 3.2±0.86. The overall success rate was 100%. Conclusions The trial of ureteroscopic lithotripsy after administering analgesics could improve the condition of elderly patients whose general condition is too poor to endure anesthesia without serious complications.